Features of Group Motivation for Criminal Acts Committed on the Grounds of Religious Hatred or Hostility - Юрчишин, Василь Миколайович; Юрчишин В. М.; Юрчишин, Василий Николаевич; Yurchyshyn, Vasyl M.; Леоненко, Тетяна Євгенівна; Леоненко, Т. Є.; Леоненко, Татьяна Евгеньевна; Leonenko, Tetiana Ye.; Леоненко, Максим Іванович; Леоненко, М. І.; Леоненко, Максим Иванович; Leonenko, Maksym I.; et al. (ASERS Publishing, 2019)
The urgency of the research is that in modern conditions the problem of legal regulation of religious relations is an important subject of attention of international organizations, scholars and the public. The article seeks to identify the features of group motivation for crimes committed on the basis of religious hatred or hostility. The article investigates the nature of social conflicts, identifies the main causes and ways of realizing interreligious conflicts and proves that these conflicts are politicized, and responsibility for resolving religious conflicts should be entrusted, first of all, to the state. The authors conclude that the totalitarian sects are the structural basis for the spread of religious extremism. The article analyzes the peculiarities of the activity of religious sects and reveals the parameters by which such organizations can be characterized as criminal.

Актуальність дослідження полягає в тому, що в сучасних умовах проблема правового регулювання релігійних відносин є важливим предметом уваги міжнародних організацій, науковців та громадськості. Стаття спрямована на виявлення особливостей групової мотивації злочинів, скоєних на ґрунті релігійної ненависті чи ворожнечі. У статті досліджено природу соціальних конфліктів, визначено основні причини та шляхи реалізації міжрелігійних конфліктів та доведено, що ці конфлікти є політизованими, а відповідальність за вирішення релігійних конфліктів має бути покладена насамперед на державу. Автори приходять до висновку, що структурною основою поширення релігійного екстремізму є тоталітарні секти. У статті аналізуються особливості діяльності релігійних сект та розкриваються параметри, за якими такі організації можна охарактеризувати як злочинні.
Leonenko T. Y. Features of Group Motivation for Criminal Acts Committed on the Grounds of Religious Hatred or Hostility / T. Y. Leonenko, M. I. Leonenko, O. O. Shkuta, V. M. Yurchyshyn // Journal of Advanced Research in Law and Economics. - Vol. 10. – Iss. 3. - ASERS Publishing, 2019. – P. 834-841.
Keywords: social conflict; interreligious conflict; extremism; terrorism; totalitarian sect; соціальний конфлікт; міжрелігійний конфлікт; екстремізм; тероризм; тоталітарна секта; Research Subject Categories::LAW/JURISPRUDENCE